STIMULATING FOODS ON TODDLERS' EATING BEHAVIOR - Wiranti, Iin; Sulistiyowati, Dwi; Wahyuni, Sri (LPPM Politeknik Saint Paul Sorong, 2024)
Background: Nutritional problems are the focus of problems in Indonesia with the main causal factor being the fulfillment of nutrients in toddlers. This is greatly influenced by toddlers' eating behavior which is formed from family parenting in meeting nutritional needs starting from serving food menus to eating habits. Efforts to improve this by stimulating growth and development by providing additional, highly nutritious food for toddlers. Research objective: to analyze the effectiveness of providing healthy snacks on toddlers' eating behavior in Langenharjo Village, Pati. Method: This type of research uses a pre-experiment with a pretest posttest group design, a purposive sampling technique of 20 toddlers aged 3-5 years with a T growth category, while the analysis uses the Shapiro Wilk test for data normality, the Wilcoxon and Mann Whitney tests to determine the effectiveness of variables study. Research results: There was an effect of providing PMT counseling on the eating behavior of toddlers with a p value of 0.002 <0.05 with the mean rank of the intervention group being higher than the control group, meaning that PMT counseling was proven to be more effective in improving the eating behavior of toddlers compared to without providing PMT. Suggestion: increase and motivate families of toddlers in providing nutritious food menus for toddlers through education.